Lack of association of HFE gene polymorphism with high body iron status in Pakistani patients with type 2 diabetes mellitus - Jibran Sualeh Muhammad; Najmul Islam; Naseema Mehboobali; Khalida Iqbal; Iqbal Azam; Mohammad Perwaiz Iqbal (Journal of the Pakistan Medical Association, 2020)
Objective: Aims of this study was to investigate the relationship of 3 common polymorphisms in the HFE gene (C282Y, H63D and S65C) with high body iron status in a population of Pakistani patients with type 2 diabetes mellitus (DM) and to explore if there is any novel mutation in HFE gene in a sample of Pakistani subjects with type 2 DM. Methods: In a case-control design, 200 healthy controls and 200 consecutive adult subjects with type 2 DM (both gender; age range of 30-70 years) were enrolled with informed consent. Their serum samples were analyzed for body iron status (ratio of concentration of soluble transferrin receptor to ferritin concentration). DNA from blood was screened for HFE gene polymorphisms via polymerase chain reaction, followed by restriction fragment length polymorphism or via Sanger sequencing to identify any novel mutation(s) in HFE gene. Results: We found that there was lack of any association between HFE polymorphism and body iron status in Pakistani subjects with type 2 DM and healthy controls. H63D was the most common polymorphism found in this population. Single base substitution of G nucleotide instead of C at the codon position 187 in the HFE gene exon 2 was discovered in one subject with DM. There was also a lack of association between D allele (variant allele of H63D) and type 2 DM. A significant relationship was found between CG genotype and abnormal albuminuria in subjects with type 2 DM (p = 0.036). Continuous...